Acessibilidade em material didático digital para idosos: estudo de caso em uma plataforma educacional digital - Marino, Mariana Cardozo Herscovici (2020)
Aging imposes limits on the body and the mind. Even in the face of these limitations - difficulty in memorizing, anomie, declining hearing and visual acuity, the elderly are returning to school, taking short courses and attending university again. Teachers, then, face a new challenge: receiving these students over 60 and including them in an effective way. The main objective of this work was to verify the ease of creating or transforming the didactic material that the teacher has in inclusive digital didactic material for these students and how much a digital platform is able to support this development. Thus, through the use of an ecosystem called SELI (smart ecosystem for learning and inclusion) still under construction, the research participants were able to test it and validate some of its features. The participation of these professionals took place in two courses - one for creating inclusive didactic material and the other for adapting didactic material, both using the ecosystem. The methodology for creating and applying the courses as well as its evaluation by the participants are presented in this work, in addition to a self-analysis of the entire process of creation and application of the courses by the author.